A comparison of assisted, resisted, and common plyometric training modes to enhance sprint and agility performance - Khodaei, K.; Mohammadi, A.; Badri, N. (The Journal of Sports Medicine and Physical Fitness, 2017)
Background: The purpose of this study was to compare the effect of assisted, resisted and common plyometric training modes to enhance sprint and agility performance. Thirty active young males (age 20.67±1.12, height 174.83± 4.69, weight 63.45± 7.51) volunteered to participate in this study that twenty-four completed testing. Methods: The participants were randomly assigned into different groups: assisted, resisted and common plyometric exercises groups. Plyometric training involved three sessions per week for 4 weeks. The volume load of plyometric training modes was equated between the groups. The posttest was performed after 48 hours of the last training session. Between-group differences were analyzed with the ANCOVA and LSD post-hoc tests, and within-group differences were analyzed by a paired T-test. Results: The findings of the present study indicated that 0-10 m, 20-30 m sprint time and the Illinois agility test time significantly decreased in the assisted and resisted plyometrics modes compared to the common plyometric training mode (p=0.05). Also, the 0-10 m, 0-30 m sprint time and agility T-test time was significantly reduced with resisted plyometrics modes compared to the assisted and common plyometric modes (p=0.05). There was no significant difference in the 10-20 m sprint time among the three plyometric training modes. Conclusions: The results of this study demonstrated that assisted and resisted plyometrics modes with elastic bands were effective methods to improve sprint and agility performance than common plyometric training in active males. Also, the resisted plyometrics mode was superior than the assisted plyometrics mode to improving sprint and agility tasks.